The verb ‘to have’ in Amharic - Laura Łykowska (Studies in African Languages and Cultures, 2000)
During my work on sentence schemata in Amharic the problem of formal description of the construction expressing "possession" appeared. Sentence schemata based on verbal centre required the verb ‘ to have’. Amharic is known for having a construction expressing "possession", but not the verb ‘ to have’. In this paper I shall make an attempt to show that contemporary Amharic has developed the verb ‘to have’ which is used apart from the construction expressing "possession". I shall also analyse the verb ‘ to have’ in terms of syntax, morphology, semantics and pragmatics.